Kajian Isu Pendidikan Islam Kontemporer - Sukari, Sukari; Setiawan, Rizka (Lembaga Yasin AlSys, 2025)
The Islamic religion has a position as rahmatan lil 'alamin, which is a pillar of moral civilization for the sake of sustainability in today's contemporary era. Handling various contemporary issues requires a comprehensive view/mindset that can provide an example and positive attitude to the new generation, especially postgraduate students of the Islamic Religious Education Study Program as carriers of a new generation of Islam who are superior in morals and manners. The aim of the research is to understand contemporary issues in Islamic education by describing problems, perspectives and problem systems accompanied by solutions. The research targets are students of the Islamic Religious Education (PAI) study program in particular and Muslims in general. The data collection technique is carried out through factual documents in the form of scientific journals, textbooks and trusted news websites. The data analysis technique uses qualitative descriptive analysis by describing information about contemporary Islamic education issues that arise and develop in everyday society. The location of this research is the Mamba'ul Ulum Islamic Institute Campus, Surakarta City with the subjects being postgraduate students of the Islamic Religious Education Study Program for the 2024/2025 academic year. Data collection uses in-depth interviews. The results of the research show that students know contemporary terms and how to deal with the world of contemporary education so that they are the right group to face the issues of Islamic education in that era. Contemporary Islamic education has crucial issues because it concerns the existence of morals and deep paradigms regarding the quality of deepening and practicing education according to the Al-Qur'an and Hadith in the current era of advanced technology. The presence of Islamic religious education and the issues that occur can give us wisdom that every era will have its challenges and be accompanied by concrete everyday solutions in accordance with Islamic principles.